Hepatic arterial infusion of oxaliplatin plus systemic chemotherapy and targeted therapy for unresectable colorectal liver metastases. (October 2020) - Boilève, Alice; De Cuyper, Astrid; Larive, Alicia; Mahjoubi, Linda; Najdawi, Milan; Tazdait, Mélodie; Gelli, Maximiliano; Tselikas, Lambros; Smolenschi, Cristina; Malka, David; Pignon, Jean-Pierre; Ducreux, Michel; et al.
Abstract: Background: Hepatic arterial infusion (HAI) combined with systemic chemotherapy has shown promising results in patients with unresectable colorectal liver metastases (CRLM), even after failure to systemic therapy. Addition of systemic targeted therapies has been investigated with controversial results regarding tolerance, especially with HAI-floruxidine when combined with systemic bevacizumab. Our study aimed to analyse feasibility, safety and efficacy of HAI-oxaliplatin plus systemic chemotherapy and targeted therapies. Methods: Between 2005 and 2016, single-centre consecutive patients with unresectable CRLM who received at least one cycle of HAI-oxaliplatin plus systemic chemotherapy and targeted therapies (cetuximab/panitumumab or bevacizumab) were analysed. Results: A total of 89 patients (median age 55 years (range, 26–76 years) who previously received a median number of one systemic chemotherapy regimen (range, 0–5) including oxaliplatin in 78% of cases were included. Median number of HAI-oxaliplatin cycles was 9 (range, 1–28) combined with systemic chemotherapy and targeted therapies (LV5FU2 [63%], FOLFIRI [36%]) plus anti-EGFR (30%), or bevacizumab (70%). Grade 3/4 toxicities included neutropenia (40%), HAI-related abdominal pain (43%) and neurotoxicity (12%). The intent-to-treat objective response rate was 42%, and 45% had stable disease, allowing complete CRLM resection/ablation in 27% of patients. After a median follow-up of 72 months, median overall and progression-free survival was 20 and 9 months, respectively. Conclusion: Addition of targeted therapy to systemic chemotherapy combined with HAI-oxaliplatin is feasible, safe and shows promising activity, even after systemic chemotherapy failure. Highlights: Hepatic arterial infusion (HAI) is promising for colorectal liver metastases (CRLM). We focused on HAI-oxaliplatin plus systemic chemotherapy and targeted therapies. Objective response rate was 41.6%, in a mostly pre-treated patient population. A complete CRLM resection/ablation was obtained in 27% of patients. It is feasible, safe and shows efficacy, even after systemic chemotherapy failure.